Methods of comparing interval objects in intelligent computer systems - Shepelev, Gennady; Khairova, N. F. (My University, 2017)
Problems of expert knowledge representation by means of generalized interval estimates approach and using methods of comparing interval alternatives in the framework of intelligent computer systems are considered. The problems are common in economy, engineering and in other domains. Necessity of multi criteria approach to comparing problem that is taking into account both preference criteria and risk ones is shown. It is proposed to use a multi-steps approach to decision-making concerning choice of preferable interval alternatives. It is based on consistent using of different comparing methods: new collective risk estimating techniques, mean-risk‖ approach (for interval-probability situations) and Savage method (for full uncertainty situations).
Keywords: interval alternatives; risk estimating techniques; collective risk assessment; mean-risk approach; generalized interval estimates